2012
DOI: 10.1099/mic.0.054775-0
|View full text |Cite
|
Sign up to set email alerts
|

Haemolysin E- and enterohaemolysin-derived haemolytic activity of O55/O157 strains and other Escherichia coli lineages

Abstract: Among three haemolysins identified thus far in Escherichia coli, alpha-haemolysin (HlyA) is encoded on the pathogenicity islands of extraintestinal pathogenic strains, while enterohaemolysin (EhxA) is encoded on the virulence plasmids of enterohaemorrhagic E. coli (EHEC) strains. In contrast, the gene for haemolysin E (HlyE) is located on the E. coli chromosome backbone and is therefore widely distributed among E. coli strains. However, because hlyE gene expression is repressed by the H-NS protein and because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 46 publications
2
19
0
1
Order By: Relevance
“…The majority of the sheA-positive strains carried other hemolysin genes, mainly ehxA; however, 63 hemolytic strains carried only sheA, suggesting that sheA might be responsible for hemolytic expression. In fact, previous studies have revealed that sheA is not totally silent in some E. coli strains, and construction of sheA deletion mutants uncovered a complete loss of hemolytic activity, indicating a sheA-dependent hemolytic phenotype (22,40,48,74). The addition of mitomycin C into the SHIBAM agar used in this study (56) may have further contributed to an increased release of sheA, presumably resulting in detectable levels of hemolytic activity (40).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The majority of the sheA-positive strains carried other hemolysin genes, mainly ehxA; however, 63 hemolytic strains carried only sheA, suggesting that sheA might be responsible for hemolytic expression. In fact, previous studies have revealed that sheA is not totally silent in some E. coli strains, and construction of sheA deletion mutants uncovered a complete loss of hemolytic activity, indicating a sheA-dependent hemolytic phenotype (22,40,48,74). The addition of mitomycin C into the SHIBAM agar used in this study (56) may have further contributed to an increased release of sheA, presumably resulting in detectable levels of hemolytic activity (40).…”
Section: Discussionmentioning
confidence: 92%
“…The addition of mitomycin C into the SHIBAM agar used in this study (56) may have further contributed to an increased release of sheA, presumably resulting in detectable levels of hemolytic activity (40). Additionally, anaerobic conditions during incubation of blood agar plates resulted in increased hemolytic expression due to sheA, and strains that were nonhemolytic under aerobic conditions expressed hemolytic activity when incubated anaerobically (22). These findings were not confirmed in our study; most of the strains either did not grow anaerobically, or hemolytic activity was decreased or completely absent compared to aerobic conditions (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All strains were tested for hemolytic activity on blood agar plates as described previously (48). Briefly, the washed blood agar plates were made with blood agar base (BBL) supplemented with 10 mM CaCl 2 and 5% defibrinated sheep blood that was washed three times in phosphate-buffered saline (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…[34][35][36][37][38][39] In E. coli, hlyE transcription is activated from a complex FNR-dependent class II promoter and HlyE activity is detected under anaerobic growth conditions. [40][41][42][43][44][45] For these enteric bacteria, oxygen starvation could signal entry into a host and prompt expression of the HlyE cytolysin. In Salmonella Typhi, the causative agent of typhoid fever, hlyE mutants exhibited impaired invasion of human epithelial (HEp-2) cells and heterologous hlyE expression in Salmonella Typhimurium enhanced colonization of the spleen and liver in a mouse model of infection.…”
Section: Introductionmentioning
confidence: 99%